2005
DOI: 10.1590/s0102-86502005000100006
|View full text |Cite
|
Sign up to set email alerts
|

Tratamento do trauma duodenal complexo: comparação entre sutura simples e sutura associada à exclusão pilórica e gastrojejunostomia em cães

Abstract: RESUMOObjetivo: Comparar uma série de parâmetros obtidos de dois tratamentos diferentes para uma lesão duodenal complexa (grau III), produzida experimentalmente. Métodos: Foram utilizados 24 cães mestiços, com peso variando entre 10 e 15 kg, divididos em 4 grupos de 6 animais. Em todos os cães provocou-se uma lesão duodenal complexa, grau III, com perda de aproximadamente 50% da sua circunferência, e realizou-se sutura no sentido longitudinal, produzindo alto grau de estenose duodenal. Nos grupos A e C realizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0
1

Year Published

2007
2007
2008
2008

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…19 In an experimental study on 30 rats subjected to pyloric exclusion with different occlusion suture materials and gastrojejunostomy with or without vagotomy, it was observed that nonabsorbable sutures maintained the pyloric closure for a longer duration (36.3 ± 11.6 days) and that vagotomy reduced the gastric inflammation without influencing the time when the pylorus should be reopened. 21 In another study from our laboratory, Pierro et al 12 compared the results from primary repair versus repair associated with pyloric exclusion and gastrojejunostomy to treat complex duodenal injuries in 24 dogs. They did not observe any differences in the incidence of duodenal stenosis, fistula formation, intraabdominal abscess or death between the two groups, but pyloric exclusion was a longer and more traumatic procedure, and it resulted in greater weight loss and increased incidence of vomiting among the animals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…19 In an experimental study on 30 rats subjected to pyloric exclusion with different occlusion suture materials and gastrojejunostomy with or without vagotomy, it was observed that nonabsorbable sutures maintained the pyloric closure for a longer duration (36.3 ± 11.6 days) and that vagotomy reduced the gastric inflammation without influencing the time when the pylorus should be reopened. 21 In another study from our laboratory, Pierro et al 12 compared the results from primary repair versus repair associated with pyloric exclusion and gastrojejunostomy to treat complex duodenal injuries in 24 dogs. They did not observe any differences in the incidence of duodenal stenosis, fistula formation, intraabdominal abscess or death between the two groups, but pyloric exclusion was a longer and more traumatic procedure, and it resulted in greater weight loss and increased incidence of vomiting among the animals.…”
Section: Discussionmentioning
confidence: 99%
“…They did not observe any differences in the incidence of duodenal stenosis, fistula formation, intraabdominal abscess or death between the two groups, but pyloric exclusion was a longer and more traumatic procedure, and it resulted in greater weight loss and increased incidence of vomiting among the animals. 12 Primary repair, pyloric exclusion without vagotomy and gastrojejunostomy were used in all the patients in this study. Duodenal injuries have been associated with high morbidity, ranging from 38% to 100%, with an average of 63.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Debido a las complicaciones de la gastroyeyunostomía, como la ulceración marginal, en nuestro servicio la evitamos y usamos la exclusión pilórica modificada con la siguiente técnica: a) cierre del píloro con sutura continua de polidioxanona 17 . Otros autores estudian, en fase experimental, el uso del polipropileno para el cerclaje pilórico 18 .…”
Section: Discussionunclassified